Digitalization and Innovation in Nigerian Firms - Olurinola, Isaiah; Osabohien, Romanus; Adeleye, Bosede Ngozi; Ogunrinola, Ifeoluwa; Omosimua, Jacob Isaac; Alwis, Tyrone De (Asian Economic and Financial Review, 2021)
This study examined the determinants of digitalization and its impact on innovation in Nigeria. The study applied the logit regression and propensity score matching (PSM) on data sourced from the World Bank 2014/2015 enterprise survey. The result from the logit regression shows that size of the firm, educational qualification of the top manager of the firm, business age, employment growth and sector of operation are the major significant determinants of the extent to which firms digitalized in Nigeria. On the other hand, the result from the propensity score matching shows that digitization is positive and significant in explaining the level of firms’ innovation in Nigeria. This means that an increased level of ICT will synonymously increase the level of firms’ ability to innovate. Based on the results, the study concludes by recommending that managers of various firms should employ a tactical approach to improve on the rate of digitization and innovation to achieve the desired level of productivity.